KINERJA DINAS PERHUBUNGAN DALAM PELAYANAN PENGUJIAN ANGKUTAN UMUM TAHUN 2020-2022 (STUDI KASUS DI KOTA MEDAN) - Cantika, Pratiwi; Sinaga, Rudi Salam; Lubis, Khairunnisah (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2023)
The background of the problem in this thesis is that the performance of the Medan city transportation service employees has not been fully effective, especially regarding testing public transportation.there are still many public transportation that are not roadworthy.this study aims to descripe and analyze employe performance in improving work quality, the research focus set includes; employee performance in completing work, employee discipline, in providing services to the public, timeliness in providing services. From the result of the study it can be concluded that the performance of employees in public service at the Medan city Transportation service. Althought they have not been able to show optimal performance, but aplicatively the employee performance achieved is indicated to be quide good.